2010
DOI: 10.1016/j.exphem.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

H1-receptor antagonists terfenadine and loratadine inhibit spontaneous growth of neoplastic mast cells

Abstract: Objective-In mast cell (MC) neoplasms, clinical problems requiring therapy include i) the local aggressive and sometimes devastating growth of MC and ii) mediator-related symptoms. A key mediator of MC responsible for clinical symptoms is histamine. Therefore, the use of histamine receptor (HR) antagonists is an established approach to block histamine effects in these patients.Methods and Results-We screened for additional beneficial effects of HR antagonists and asked whether any of these agents would also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 41 publications
1
34
0
1
Order By: Relevance
“…For prophylaxis of recurrent episodes of anaphylaxis or persistent pruritus, antihistamines should be administered daily. In vitro antihistamines have been shown to inhibit spontaneous growth of neoplastic mast cell lines [42]. Whether this also affects in vivo neoplastic mast cell growth remains to be determined.…”
Section: Therapy For Cutaneous and Indolent Systemic Mastocytosismentioning
confidence: 99%
“…For prophylaxis of recurrent episodes of anaphylaxis or persistent pruritus, antihistamines should be administered daily. In vitro antihistamines have been shown to inhibit spontaneous growth of neoplastic mast cell lines [42]. Whether this also affects in vivo neoplastic mast cell growth remains to be determined.…”
Section: Therapy For Cutaneous and Indolent Systemic Mastocytosismentioning
confidence: 99%
“…The second generation of H1 receptor blocking agents including loratadine (LRT), can be used for inhibiting histamine release from the basophilic granulocytes and the mastocytes where histamine is stored in tissues [3]. LRT displays various side effects including several allergic reactions including rash, hives, itching, difficulty in breathing, tightness in the chest, swelling of the mouth or face and dizziness during systemic administration by oral route.…”
Section: Introductionmentioning
confidence: 99%
“…Based on in vitro experiments, certain second‐generation H1R blockers, such as rupatadine, azelastine, epinastine, or olopatadine, may act not only by blocking histamine binding to its receptors, but also by inhibiting MC degranulation . Moreover, we have observed that the H1R antagonists terfenadine and loratadine suppress spontaneous growth of neoplastic MCs in vitro . However, such effects are observed at relatively high drug concentrations that might not be reachable in vivo .…”
Section: Management Of Mediator‐related Symptomsmentioning
confidence: 99%